Threshold enhancement of diphoton resonances - Aoife Bharucha; Abdelhak Djouadi; Andreas Goudelis (Physics Letters B, 2016)
We revisit a mechanism to enhance the decay width of (pseudo-)scalar resonances to photon pairs when the process is mediated by loops of charged fermions produced near threshold. Motivated by the recent LHC data, indicating the presence of an excess in the diphoton spectrum at approximately 750 GeV, we illustrate this threshold enhancement mechanism in the case of a 750 GeV pseudoscalar boson A with a two-photon decay mediated by a charged and uncolored fermion having a mass at the 12MA threshold and a small decay width, <1 MeV. The implications of such a threshold enhancement are discussed in two explicit scenarios: i) the Minimal Supersymmetric Standard Model in which the A state is produced via the top quark mediated gluon fusion process and decays into photons predominantly through loops of charginos with masses close to 12MA and ii) a two Higgs doublet model in which A is again produced by gluon fusion but decays into photons through loops of vector-like charged heavy leptons. In both these scenarios, while the mass of the charged fermion has to be adjusted to be extremely close to half of the A resonance mass, the small total widths are naturally obtained if only suppressed three-body decay channels occur. Finally, the implications of some of these scenarios for dark matter are discussed.